Pengembangan Aset Wisata Edukasi Kebudayaan Flashcards Berbasis Augmented Reality untuk Pembelajaran Seni dan Budaya TK Laboratorium - Muhammad Syifa'ul Qolbi; Alby Aruna; Mohamad Firzon Ainur Roziqin; Iriaji; Eka Putri Surya; Adinda Marcelliantika; Ginanjar Atma Wijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of cultural educational asset flashcards based on Augmented Reality (AR) for art and culture learning at TK Laboratorium aims to enhance children's interest and understanding of local arts and culture. This program integrates AR technology with educational flashcards to create an interactive and engaging learning experience. Methods include the design and development of AR flashcards, technical training for teachers, and effectiveness evaluation through user feedback. Results show a significant increase in children's engagement and understanding of art and cultural materials. The implementation of this program is expected to support the development of innovative and effective art and culture learning at the early childhood education level.